Perkembangan Pendidikan Bahasa Arab di Era Digital: Sistematic Literature Review - Aunur Shabur Maajid Amadi; Dina Wilda Sholikha (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
Arabic language education holds a pivotal role in global intellectual and cultural development as the language of the Quran and profound literary works. However, the era of globalization and digital technology presents new challenges and opportunities. Teaching methods and access to information have undergone transformative changes due to technological advancements (Muis, 2020). Addressing this, a systematic literature review is warranted to comprehend the development of Arabic language education in the digital age. This research focuses on the development of digitally-based learning materials, applications and platforms for Arabic language education, the effectiveness of technology-based teaching methods, as well as their impact on Arabic language proficiency and student motivation. Challenges and potential solutions in adopting technological approaches will also be analyzed. Employing a qualitative approach, this study employs a systematic literature review method to extract insights from various literary sources. The anticipated outcome will provide educators with valuable guidance on leveraging technology effectively in Arabic language education and navigating the evolving dynamics of education in the digital era.